"Digital Twins" in Education: Prospects and Reality - V. V. Vikhman; M. V. Romm (Moscow Polytechnic University, 2021)
This article is aimed at understanding the revolutionary in meaning and "digital" in essence metamorphoses in education and the prospects for the emergence of a new educational network reality based on them. The focus of the discussion is not so much on digital innovations and transformations in education as such, but rather on the need to understand the possible prospects and results of these social network changes and modifications brought to life by the next stage of the digital revolution in education. It is proposed to include a wide range of network technologies and methodologies among the latest scientific and technological innovations taking into account the fact that the main focus of the work is on understanding the process / result of implementing the methodology of "digital twins" in education. Despite the fact that the latter is only at the beginning of its implementation in a broad educational context, the paper raises the question of the social consequences of implementing the methodology for constructing the latest network reality of "digital twins in education", which has all the chances in the future to become a unique network of networks of "digital twins" of various social actors in education. The article discusses the managerial potential of developing and the difficulties of implementing the digital twin methodology, the expected effects of implementing the latter in education, and the socio-technological consequences of converting this technology into a new network educational reality in the Russian Federation.